2002
DOI: 10.1051/0004-6361:20020172
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of unusual large group delay in microwave millisecond oscillating events

Abstract: Abstract. Two events demonstrating periodic narrowband millisecond pulsations of radio emission both in intensity and polarization degree are analyzed. Large time delays between L-and R-polarization components are found. The radio emission is shown to be generated as unpolarized by a plasma mechanism at the second harmonic of the upper-hybrid frequency. Observed oscillations of the radiation polarization degree arise due to group delay between extraordinary and ordinary modes along the line of sight. The theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 15 publications
4
26
1
Order By: Relevance
“…They found a delay of approximately 100 μs between different spike polarities. The group delay for pulsations was studied by Fleishman et al (2002) who reported a delay of up to 20 ms in an exceptional event at 2.8 GHz.…”
Section: Origin Of Delaysmentioning
confidence: 99%
“…They found a delay of approximately 100 μs between different spike polarities. The group delay for pulsations was studied by Fleishman et al (2002) who reported a delay of up to 20 ms in an exceptional event at 2.8 GHz.…”
Section: Origin Of Delaysmentioning
confidence: 99%
“…For completeness, we mention that the presence of a magnetic field renders a plasma birefringent and causes radiation at a fixed frequency to show a differential delay between the ordinary and extraordinary modes, which corresponds to a delay between RCP and LCP emissions. At frequencies where 3 pe and Be , the differential group delay between RCP and LCP over a path from the region of source emission to observation is (Benz & Pianezzi 1997;Fleishman et al 2002aFleishman et al , 2002b)…”
Section: Propagation Effectsmentioning
confidence: 99%
“…Solar microwave bursts often display quasi-periodical pulsations with periods from ≈40 ms in narrowband bursts (Fleishman et al 2002) up to 20 s in broadband bursts (Nakajima 1983;Stepanov et al 1992;Qin et al 1996;Asai et al 2001). Broadband microwave bursts are generated by the gyrosynchrotron emission mechanism which is very sensitive to the magnetic field in the radio source.…”
Section: An Observational Examplementioning
confidence: 99%